Regioselective TfOH-mediated hydroamidation of ynamides with nitriles. Issue 19 (11th May 2017) - Wang, Wan-Shu; Chen, Ping; Tang, Yu
Abstract: A new TfOH-mediated reaction of ynamides with nitriles as nucleophiles has been developed. The reaction works efficiently under mild reaction conditions to afford a new class of α-acylaminoenamides readily via the intermediacy of keteniminium ion. The reaction displays generality and a broad substrates scope. Additionally, the α-acylaminoenamides could be transformed to highly substituted pyridine, 4-aminopyrimidine or isoquinoline cores. Graphical abstract: